Small intestinal function and dietary status in dermatitis herpetiformis. - Gawkrodger, D J (1991)
Small intestinal morphology and function were assessed in 82 patients with dermatitis herpetiformis, 51 of whom were taking a normal diet and 31 a gluten free diet. Methods used were histopathological evaluation of jejunal mucosal biopsy specimens, quantitation of intraepithelial lymphocytes, cellobiose/mannitol permeability test, tissue disaccharidase values, serum antigliadin antibodies, and formal assessment of dietary gluten content by a dietician. There was no correlation between dietary gluten intake and the degree of enteropathy in the 51 patients taking a normal diet, whereas biopsy specimens were normal in 24 of the 31 patients on a gluten free diet, all previously having been abnormal. Eighteen patients on gluten containing diets had normal jejunal histology and in seven of these all tests of small intestinal morphology and function were entirely normal. Intestinal permeability was abnormal and serum antigliadin antibodies were present in most patients with enteropathy. Studies of acid secretion in seven patients showed that hypochlorhydria or achlorhydria did not lead to abnormal permeability in the absence of enteropathy. This study shows that a combination of objective tests of small intestinal architecture and function will detect abnormalities in most dermatitis herpetiformis patients, including some with histologically normal jejunal biopsy specimens. Nevertheless there is a small group in whom all conventional intestinal investigations are entirely normal.